Toxic effects of the methanol extracts of some tunicate species - Ibrahim Jantan,; Zeti Azura Mohamed Hussein,; Alma Awaluddin,; Nazni Wasi Ahmad, (penerbit ukm, 2004)
The toxicities of the methanol extracts of seven tunicates (Phallusia sp., Eudistoma obscuratum, Atriolum robustum, Didemnum sp., D. molle, Clavelina picta and Aplidium sp.) on brine shrimp and the 4th instar larvae of four vector mosquitoes (Culex quinquefasciatus, Anopheles maculatus, Aedes aegypti and Ae. albopictus) were investigated. The extracts were very toxic to the brine shrimp with LC50 values ranging from 0.8 – 26.0 mg/ml and the most toxic being the extract from Aplidium sp. The extracts were also effective against the mosquito larvae with LC50 values ranging from 1.2 – 55.6 mg/ml. Larvicidal activity of the extracts was most significant on An. maculatus with LC50 values ranging from 1.2 – 6.2 mg/ml and of these, the most toxic was the extract of E. obscuratum.